2016
DOI: 10.1371/journal.pone.0161178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strength Training on Oxidative Stress and the Correlation of the Same with Forearm Vasodilatation and Blood Pressure of Hypertensive Elderly Women: A Randomized Clinical Trial

Abstract: The aim of the study was to evaluate the effect of strength training on oxidative stress and the correlation of the same with forearm vasodilatation and mean blood pressure of hypertensive elderly women, at rest (basal) and during a static handgrip exercise. Insufficiently active hypertensive elderly women (N = 25; mean age = 66.1 years) were randomized into a 10 week strength training group (n = 13) or control (n = 12) group. Plasma malondialdehyde (MDA), total antioxidant capacity (TAC), plasma nitrite (NO2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 52 publications
1
26
0
6
Order By: Relevance
“…Table 4 shows the risk of bias evaluated with Cochrane Scale. Two studies presented high risk [27,29]; two presented uncertain risk [28,30]; and one presented low risk of bias [10]. Most of the studies failed to comply with the domains "randomization" and "allocation concealment."…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 shows the risk of bias evaluated with Cochrane Scale. Two studies presented high risk [27,29]; two presented uncertain risk [28,30]; and one presented low risk of bias [10]. Most of the studies failed to comply with the domains "randomization" and "allocation concealment."…”
Section: Resultsmentioning
confidence: 99%
“…Several studies, including meta-analyses, have investigated the effects of physical exercise on the reduction of blood pressure in normotensive and hypertensive individuals of different age groups [6][7][8][9]. Cardiorespiratory training [CT] is known to increase the maximal oxygen consumption in older adults [10], maintain resistance to oxidative stress and improve lifestyle [11] with its effects on blood pressure, which is well established in the literature. CT is therefore suggested as a complementary treatment for hypertension [12].…”
Section: Palabras Clave: Resistencia De Entrenamiento Edad Hipertenmentioning
confidence: 99%
“…The role of ROS in exercise is of considerable interest to researchers. 47 High levels of MDA are used as markers of OS during acute exercise, and exercise-induced apoptosis is a regulatory process designed to eliminate damaged cells without producing a significant inflammatory response, thus ensuring optimal body function. 48 Malondialdehyde production has been reported to decrease after regular resistance exercise training.…”
Section: Relationship Between the Molecules Associated With Os And Thmentioning
confidence: 99%
“…6 Dantas et al showed a reduction in MDA and an increase in total antioxidant capacity (TAC) after strength training among elderly women. 7 In another study Pedersen et al indicated that daily taking of methylsulfonylmethane supplement for 10 days can reduce muscle damage by affecting TAC in healthy men. 8 The biological effects of oxidizing compounds in the body are controlled by antioxidant factors.…”
mentioning
confidence: 99%